A new agent approach for recognizing research trends in wearable systems. (July 2017) - Aljawarneh, Shadi A.; Elkobaisi, Mohammed R.; Maatuk, Abdelsalam M.
Abstract: In this article, a new agent approach has been proposed for recognizing the research trends in wearable systems. In addition, we have formulated a mathematical model to predict the agent development trends in the field of wearable systems. The proposed agent approach converts the raw documents found on the Internet into relevant information. To determine the key trends, we traced and analyzed the behavior of the agent development aspects using keywords over a long period. A prototype has been developed in order to search for multiple keywords at the same time and collect the required data automatically to eliminate the useless data. Subsequently, the required data is converted into usable information. The results showed that the research trends in wearable systems are divided into four zones: growing, slowing down, decreasing gradually, and quickly decreasing zones.